2008
DOI: 10.4314/ajtcam.v4i4.31238
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-Veterinary Practices Amongst Small–Holder Farmers In Ekiti State, Nigeria

Abstract: This paper aimed at identifying factors influencing the use of ethno-veterinary practices amongst goat and poultry farmers in Ekiti state, Nigeria. It specifically described the socio-economic characteristics of the farmers; identified some diseases of goats and poultry with their corresponding indigenous cures; presented the procedures used in developing some of the ethno-veterinary medicine amongst farmers; identified the reasons for using ethnoveterinary practices; analysed the ecological factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…Turmeric paste is used for prevention and treating different skin diseases including fungal infections (Mishra, 2011;Rautray et al, 2015). The present result agrees with the findings of Kolawole et al (2007) that palm oil is used to treat scabies (mange). It also corroborates Ojo et al (2014) whose respondents used Khaya senegalensis and Nicotiana tabacum to treat mange in ruminants in Ekiti State, Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…Turmeric paste is used for prevention and treating different skin diseases including fungal infections (Mishra, 2011;Rautray et al, 2015). The present result agrees with the findings of Kolawole et al (2007) that palm oil is used to treat scabies (mange). It also corroborates Ojo et al (2014) whose respondents used Khaya senegalensis and Nicotiana tabacum to treat mange in ruminants in Ekiti State, Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that a high percentage of the respondents were within economic productive age and are still active in herding and taking care of their cattle. The findings of the research corroborate that of Kolawole et al (2007) in a study they conducted on ethno-veterinary practices amongst smallholder farmers in Ekiti state, Nigeria. Result in Table 1 also revealed that only 24.30% of the respondents had formal education (out of which 20.56% had primary and 3.74% attained secondary education) while 75.70% of the respondents had no formal education.…”
Section: Resultssupporting
confidence: 81%
“…The use of the botanicals in the town is diminishing because they are switching to modern medicine to treat ruminant diseases. Diarrhea and mange were the most diseases and pest affecting the ruminant in the area (Adeola et al, 2014;Kolawole et al, 2007). Indigenous knowledge can be applied to treat ruminant New species of goat were found in Ilara-mokin (Grey, White and Black) compared to that of Ekiti state (Black, Brown) and that of sheep (Black) in Ilara-mokin and white in Ekiti state.…”
Section: Discussionmentioning
confidence: 99%